2002
DOI: 10.1182/blood.v99.4.1332
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the gene encoding the transcription factor CCAAT/enhancer binding protein α in myelodysplastic syndromes and acute myeloid leukemias

Abstract: The CCAAT/enhancer binding protein ␣ (C/EBP␣) protein is essential for proper lung and liver function and granulocytic and adipose tissue differentation. It was hypothesized that abnormalties in C/EBP␣ function contribute to the development of malignancies in a variety of tissues. To test this, genomic DNA from 408 patient samples and 5 cell lines representing 11 different cancers was screened for mutations in the C/EBP␣ gene. Two silent polymorphisms termed P1 and P2 were present at frequencies of 13.5% and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
251
2
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(267 citation statements)
references
References 53 publications
(82 reference statements)
12
251
2
2
Order By: Relevance
“…C/EBPA mutations were first described by Pabst et al in 2001 [9], and have subsequently been observed by many other investigators with the frequency of 5-14% in de novo AML [5][6][7][8][9]. The gene mutation is composed of base pair substitutions, deletions, and insertions and can be largely divided into two common types: First, carboxy-terminal in-frame mutations which disrupt the basic zipper region, thus affecting DNA binding as well as homodimerization and heterodimerization with other C/EBP family members.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…C/EBPA mutations were first described by Pabst et al in 2001 [9], and have subsequently been observed by many other investigators with the frequency of 5-14% in de novo AML [5][6][7][8][9]. The gene mutation is composed of base pair substitutions, deletions, and insertions and can be largely divided into two common types: First, carboxy-terminal in-frame mutations which disrupt the basic zipper region, thus affecting DNA binding as well as homodimerization and heterodimerization with other C/EBP family members.…”
Section: Introductionmentioning
confidence: 88%
“…Growing evidence indicates that the key function of C/EBPA gene can be altered by a number of mechanisms, such as gene mutation, transcriptional dysregulation, as well as epigenetic modification in leukemic cells of AML patients, and the functional inactivation of C/EBPA has become a pathophysiological signature of myeloid leukemia. The events leading to the loss of C/EBPA function facilitate leukemogenesis by blocking granulocytic differentiation in hematopoiesis of AML patients [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Genomic DNA was isolated form Bone marrow/peripheral blood samples and four overlapping primer pairs were used to amplify the entire CEBPA coding region giving 306bp, 309bp, 366bp and 266bp for the four fragments respectively (Gombart et al, 2002). PCR-SSCP analysis was performed for mutation detection.…”
Section: Molecular Analysismentioning
confidence: 99%
“…The two C/EBPα isoforms exhibit similar biological functions; for example, both C/EBPαp42 and C/EBPαp30 can transactivate promoters of aP2 and C/EBPα [23]. However, in certain cases C/EBPαp30 acts as a dominant-negative regulator of C/EBPαp42 [26,27].…”
Section: Introductionmentioning
confidence: 99%